Marine Biodiversity of Coral Reef Fishes in Pieh Marine Recreational Park After Bleaching and Acanthaster Outbreaks - Risandi Dwirama Putra; Muhammad Abrar; Rikoh Manogar Siringoringo; Ni Wayan Purnamsari; Pradipta Agustina; MD Jayedul Islam (Jurnal Ilmiah Perikanan dan Kelautan, 2022)
Highlight ResearchAfter bleaching disturbance and Acanthaster planci outbreaks, herbivore fishes species were dominated in MRP PiehThis explains the marine recreational activities in utilization zone MRP Pieh have no impact on reducing fish biomassAfter disturbance in MRP Pieh shows the coral reef fishes still endurance on bleaching event, and Acanthaster planci outbreak after disturbance in MRP Pieh shows the coral reef fishes still endurance on bleaching event and Acanthaster planci outbreak. However, the composition of corallivorous has decreased but has been an increase in herbivorous and carnivorous fish populationsAbstractPieh MRP encountered non-anthropogenic phenomena, precisely massive coral bleaching in 2016, 2017, and massive predators from Acanthaster planci outbreaks in 2018. This study aimed to understand the pattern of coral reef diversity in the core zone and utilization in the MRP area and compare it to non-MRPS locations that accept the same non-anthropogenic pressure conditions. Coral fish sampling using a UVC is categorized into three zones: the core zone, the utilization zone, and outside the MRP area. 8 Families of coral reef fishes were counted based on categories of level function in ecologies and economy. Taxonomic distinctiveness estimates were calculated mathematically for each sample, including species richness and taxonomic diversity were compared among zonation area. Pearson's Coefficient Correlation Matrix was used to measure the correlation relationship between zonation areas. There are 91 species of fish and 3002 individuals found. The richest family in the MRP Core Zone and MRP Utility Zone was Acanthuridae with 20 species and non-MRP has a lower species richness and abundance of fish communities. The dominant species in Pieh MRP was Ctenochaetus striatus with average abundant per site (21.3 ± 7.62, n = 3). Acanthuridae represents 55.98% of the total biomass in MRP-Core Zone, 63.13% in MRP-Utility Zone, and 41.55% in Non-MRP Area. This study showed the number of species and populations from corallivores fishes have decreased but has been an increase in herbivorous and carnivore diversity. The diversity indices (H') and ENS also shows no differ significantly between zonation.